PENTINGNYA AUDIT DAN AKUNTANSI SYARIAH ERA INDUSTRI 4.0 DI INDONESIA - Wardani, Anisa Ayu; Fajar Sari, Dini Putri (KEADABAN: Jurnal Sosial dan Humaniora, 2023)
The lack of socialization and neglect of Islamic auditing and accounting in today's digital world is the basis of this research. This study aims to find out the urgency of sharia auditing and accounting if implemented in Indonesia, especially during a disruptive period like today. When the existence of Islamic auditing and accounting which continues to experience development in the scope of Islamic economics has created its own obstacles, especially in Indonesia. The concept of this research using subjective information investigation. This study found that sharia audits are urgently needed, especially in Islamic banks and non-bank institutions in Indonesia. From the accounting system used to ensure the excellence of Islamic banks or financial institutions in Indonesia. Sharia accounting is needed to increase the value of company branding, especially in the era of disruption (industrial era 4.0).Abstrak: Minimnya sosialisasi dan pengabaian audit dan akuntansi syariah di dunia digital saat ini menjadi landasan penelitian ini. Kajian ini bertujuan untuk mengetahui urgensi audit dan akuntansi syariah jika diterapkan di Indonesia, khususnya di masa disrupsi seperti saat ini. Ketika keberadaan audit dan akuntansi syariah yang terus mengalami perkembangan dalam lingkup ekonomi syariah telah menciptakan hambatan tersendiri, khususnya di Indonesia. Konsep penelitian ini dengan menggunakan penyelidikan informasi subyektif. Studi ini menemukan bahwa audit syariah sangat dibutuhkan, khususnya di bank syariah dan lembaga non bank di Indonesia. Dari sistem akuntansi yang digunakan untuk memastikan keunggulan bank atau lembaga keuangan syariah di Indonesia. Akuntansi syariah diperlukan untuk meningkatkan nilai branding perusahaan, khususnya di era disrupsi (era industri 4.0).